Predicting Couple Resilience Based on Faith: The Mediating Role of Forgiveness in Christian Marriages - Alya Padji Happu; Pradipta Christy Pratiwi (Journal of Educational, Health and Community Psychology, 2026)
The present study examines whether forgiveness mediates the relationship between faith in God and couple resilience among Christian married couples. Using a quantitative, correlational design, we collected data from 254 married Christians in Indonesia via an online questionnaire assessing faith, forgiveness, and couple resilience. We conducted a mediation analysis with bootstrapping to estimate indirect effects. The results indicate that faith is positively associated with forgiveness. However, faith is not significantly directly associated with either the positive or negative dimensions of couple resilience. Instead, the relationship between faith and couple resilience appears to operate primarily through forgiveness: higher faith is linked to greater forgiveness, which in turn strengthens positive couple resilience and reduces negative couple resilience. These findings suggest that faith supports marital resilience mainly by fostering relational practices, rather than serving as a direct predictor of resilient functioning. The study highlights forgiveness as a key interpersonal mechanism through which faith-based values are enacted within marriage and underscores the value of incorporating forgiveness-focused components into faith-based marital and premarital interventions.